Correction: Ameliorative role of camel whey protein and rosuvastatin on induced dyslipidemia in mice. Issue 6 (24th May 2018) - El-Shinnawy, Nashwa Ahmed; Abd-Elhalem, Sahar Sobhy; Haggag, Nawal Zakaria; Badr, Gamal
Abstract : Correction for 'Ameliorative role of camel whey protein and rosuvastatin on induced dyslipidemia in mice' by Nashwa Ahmed El-Shinnawy et al., Food Funct., 2018, 9, 1038–1047.